IMD: A Software Package for Molecular Dynamics Studies on Parallel Computers - Stadler, J.; Mikulla, R.; Trebin, H.-R. (International journal of modern physics. C, Computational physics, physical computation, 1997)
We report on implementation and performance of the program IMD, designed for short range molecular dynamics simulations on massively parallel computers. After a short explanation of the cell-based algorithm, its extension to parallel computers as well as two variants of the communication scheme are discussed. We provide performance numbers for simulations of different sizes and compare them with values found in the literature. Finally we describe two applications, namely a very large scale simulation with more than 1.23×109 atoms, to our knowledge the largest published MD simulation up to this day and a simulation of a crack propagating in a two-dimensional quasicrystal.